Scaling and Spatial Analysis of Infiltration at the Regional Scale (Case Study: the Shahrekord Watershed) - gh. a; m.r k; e. s (مهندسی منابع آب, 2014)
Some Experiments were conducted in water research center, for five specific discharge and four tail water depth to investigate effects of parameters like specific discharge and tail water depth.  To carry out the experiments we made use of the hydraulic model of Azad dam. Measured parameters are: Maximum depth of scour, distance of maximum scour depth from bucket, the maximum length of scour hole and maximum width of scour hole. By using nonlinear regression analysis to predict the scour hole dimensions some relations were achieved. These relations were tested by applying experimental data from other investigators. in this research The results have showed  the relative ability of the presented relations. Scour wide and the place of maximum depth are estimated appropriately by using of these relations. The relation of maximum depth is compared with another famous relations and showed weaker results. The best results was for Martins B relation.